Analysis of Interaction between Interior and Exterior Wall Corrosion Defects - Zhanhui Wang; Mengzhao Long; Xiaojun Li; Zhifang Zhang (Journal of Marine Science and Engineering, 2023)
With the increase in oil and gas pipe mileage, various corrosion defects inevitably occur, so the mechanisms and the applicability of the interaction corrosion defects are investigated. The ANSYS Workbench software is used to study the three double defect pipe models based on the exterior wall, the interior wall, and the interior and exterior wall. First, the distribution of the stress nephogram is investigated. Second, the failure pressure is obtained through the load step based on the variety of the failure pressure. Finally, the critical distance formula of the different types of double defect pipe models is fitted using MATLAB software, and its applicability and accuracy are verified. The results show that the equivalent stress is divided into two areas; with increasing defect depth and defect length, the critical distance increases and the growth rate increases; by fitting the critical distance formula of the three double defect pipe models, the multiple function formula of defect depth and defect length under different defect location distribution is obtained, with high accuracy. The critical distance ratio is introduced to compare 150 sets of data of the 3 models for conservative calculation; the three models perform well in the critical distance ratio and the double defect pipe model based on the exterior wall is the most conservative.